Global Wheat Production - Fahad, Shah; Basir, Abdul; Adnan, Muhammad (IntechOpen, 2018)
Global wheat consumption in the 2016/2017 season is forecasted to reach a record high 736m tonnes, showing a growth of 25% in the last 15 years. This raises the question which outlets the wheat is going into, what the growth of these outlets is, which regions or countries have grown the most, and where do we see future potential. Strong competition of other feed grains like corn is expected to slow the growth of wheat used for feed in the next years, and in the future, companies involved in the grain supply chain and feeding industry will need to be flexible enough to continue to meet this fast-changing demand for feed grains. For feed producers, this means they need to be able to access supplies of different grains from different origins to allow for the cheapest composition of their feed, while grain suppliers need to be able to continuously best engage with global trading opportunities to originate grains in various regions and move them to demand regions as cost-effectively as possible.